3D-printed porous titanium versus polyetheretherketone cages in lateral lumbar interbody fusion: a systematic review and meta-analysis of subsidence - Liu, Shu-Xin; Zeng, Teng-Hui; Chen, Chien-Min; He, Li-Ru; Feng, An-Ping; Jhang, Shang-Wun; Lin, Guang-Xun (Frontiers in Medicine, 2024)
Background Cage subsidence frequently complicates lumbar fusion procedures, including lateral lumbar interbody fusion (LLIF), potentially leading to recurrent pain, impaired fusion, and accelerated degeneration of adjacent segments. A critical factor influencing cage subsidence is the selection of material. Polyetheretherketone (PEEK) and three-dimensional printed titanium (3D-Ti) cages are commonly used in LLIF procedures, each offering distinct advantages. However, these materials possess inherent property differences that may translate into divergent settling rates. To contribute to this discourse and offer insights, this systematic review and meta-analysis aims to compare the rates of cage subsidence between 3D-Ti and PEEK cages in LLIF. Methods A meticulous systematic search that employs distinct MeSH terms was conducted in major electronic databases (MEDLINE, PubMed, Embase, Scopus, Web of Science, and Cochrane) up to December 20, 2023. The quality of inclusion was measured using the Newcastle-Ottawa Scale (NOS) for non-randomized trials. The primary outcome measure was cage subsidence, while the secondary outcome involved evaluating subsidence within each treatment segment using the Marchi classification. Results The review included 265 patients (441 segments) from three studies. All with NOS ratings exceeding 5 stars. In the analysis, 189 segments (42.9%) underwent LLIF with 3D-Ti cages, while 252 segments (57.1%) participated in LLIF with PEEK cages. Overall, the cage subsidence rate was significantly lower with 3D-Ti compared to PEEK (p < 0.00001, OR = 0.25; 95% CI 0.14 to 0.44). Specifically, the 3D-Ti group exhibited a markedly lower subsidence rate, categorized by grade I, II, and III, compared to the PEEK group (p < 0.05). Furthermore, the incidence of severe subsidence was significantly reduced in the 3D-Ti group compared to the PEEK group (p = 0.0004, OR = 0.17; 95% CI 0.07 to 0.46). Conclusion The study concludes that the subsidence rate associated with 3D-Ti cages in LLIF is notably lower than that observed with PEEK cages, underscoring the potential advantages of 3D-Ti cages in mitigating cage subsidence.